Impelementasi Model Pendidikan Tasawuf dalam penguatan Peace Education dan Moderasi Beragama di Yayasan Pesantren Ahlus Shafa wal Wafa Sidoarjo - Saifuddin, Saifuddin (Proceedings of Annual Conference for Muslim Scholars, 2024)
Sufism, the embodiment of ihsan, emphasizes respect for all creatures, regardless of background. It promotes tolerance and peace, aligning with the Islamic principle of rahmatan li al-'alamin. Peace education, a core component of Sufism, fosters respect for differences, tolerance, and mutual understanding. This study explores the implementation of Sufism education at the Ahlus Shafa wal Wafa Islamic boarding school. The school utilizes various activities, including Sufism book studies, socio-religious activities, ubudiyah practices, Islamic art, and interfaith dialogue. These activities strengthen Islamic brotherhood, national brotherhood, and universal brotherhood, ultimately fostering peace education and religious moderation.